Ethical and Professional Transformations in the Employment of Artificial Intelligence Technologies in the Digital Media Content Industry - Abu Draz, Ahed Maher (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to identify the ethical and professional transformations in the use of artificial intelligence technologies in the digital media content industry. It also aimed to assess the level of awareness of media professionals and academics in the field of media about the impact of artificial intelligence technologies on the ethical and professional dimensions of the digital media content industry. Methods: The study followed a survey approach, and the study population consisted of all media professionals and academics in the field of media in the United Arab Emirates. The questionnaire was distributed electronically, and 160 questionnaires were retrieved, representing the actual study sample. Results: The study results showed that the most important ethical and professional transformations imposed by artificial intelligence technologies in digital media institutions are the replacement of some jobs with artificial intelligence technologies, changing the way sources are accessed, changing the methods and techniques of research and information gathering, and changing the methods of content building. The level of assessment of the ethical dimensions imposed by artificial intelligence technologies in digital media institutions came with a relative weight of 67.797, which is at a medium level of agreement. Conclusions: The study recommended the need to benefit from artificial intelligence technologies in the digital media content industry, to reduce the negative effects of artificial intelligence technologies in the field of digital media.